Cloud Resourse Virtualization - Tayyaba, Kalburgi; Ibrahim, Md; Sajjan, RS (International Journal of Computer Sciences and Engineering, 2025)
Internet, it is a large collection of networks where resources are globally networked, in internet cloud computing plays a major role in order to share the data and one of the important technology in the cloud computing is virtualization. Mainly it is used to maintain the collection IT resources which are used by the cloud providers. The main aim of the virtualization is ability to run the multiple operating systems on a single machine buy sharing all the resources that belong to the hard ware as well as it enables industry or academic IT resources through on-demand allocation dynamically. The resources have different forms such as network, server, storage, application and client. In this paper our main goal is to provide the basic knowledge about the virtualization technology in cloud computing and how it acts in the cloud computing environment. And we also discuss about, how to maintain the virtualized environment with the optimized resources.